THE APPLICATION OF TOTAL QUALITY MANAGEMENT IN MAINTAINING PRODUCT QUALITY TO INCREASE CONSUMER SATISFACTION AT RGB PRINTING IN SAMARINDA - Nadia Aulia Putri Kustaniah; Mukhibatul Hikmah; Muhammad Zaini; Poppy Alvianolitan Sanistasya (Proceedings International Indonesia Conference on Interdisciplinary Studies, 2025)
The influence of globalization in today's industry has increased the level of competition between companies, making them increasingly fierce and competitive. A company's success is often measured by the quality of the products it produces. Total Quality Management (TQM) is an ongoing process that aims to achieve better quality standards in meeting customer needs. This study aims to analyze the application of Total Quality Management (TQM) in maintaining product quality and its impact on consumer satisfaction at RGB Printing in Samarinda. TQM is a management approach that focuses on overall quality improvement through continuous improvement, involvement of all members of the organization, and orientation to customer satisfaction. This study uses a qualitative method with a descriptive approach, where data is collected through interviews, observations, and documentation. The results of the study show that the implementation of TQM in RGB Printing involves strict supervision of the production process, improving the quality of raw materials, and training employees regularly. In addition, the Plan-Do-Check-Act (PDCA) method is used to ensure that each stage of production runs according to the standards that have been set. The impact of the implementation of TQM on product quality can be seen from the decrease in product defects and the improvement of mold quality. In addition, the implementation of TQM also has a positive impact on consumer satisfaction, which is reflected in the increase in the number of repeat customers and the reduction in complaints about print results. Overall, this study emphasizes that TQM strategies that are consistently applied can increase the company's competitiveness through improved product quality and more optimal customer satisfaction.